2021
DOI: 10.1089/zeb.2020.1928
|View full text |Cite
|
Sign up to set email alerts
|

An Endeavor to Find Starter Feed Alternatives and Techniques for Zebrafish First-Feeding Larvae: The Effects on Viability, Morphometric Traits, Digestive Enzymes, and Expression of Growth-Related Genes

Abstract: Low and variable growth and survival rates (SR) of 6-10 days post-fertilization zebrafish larvae are a problem. This problem seems to be linked to starter feed characteristics. The present study is an attempt to find alternatives to address these requests. For this, larvae were fed fresh and lyophilized microalgae (Chlorella, Scenedesmus, and Haematococcus), egg yolk (YOLK), lyophilized Artemia nauplii (LAN) and a combination of them. The lowest SR was observed in algae-fed larvae. All died on day 11 showing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…24 Feeding regimens and nutritional sources are not standardized across labs, 62 but chicken egg yolk is a recently introduced feed 63 that provides sufficient nutrition. 64 We demonstrated that introduction of chicken egg yolk emulsion to larvae between 5 and 7 dpf caused a significant increase in pRCs and trending increase in pACs. Our findings confirmed and expanded upon prior findings.…”
Section: Fed State Increases Proximal Midgut-originating Anterograde ...mentioning
confidence: 71%
See 1 more Smart Citation
“…24 Feeding regimens and nutritional sources are not standardized across labs, 62 but chicken egg yolk is a recently introduced feed 63 that provides sufficient nutrition. 64 We demonstrated that introduction of chicken egg yolk emulsion to larvae between 5 and 7 dpf caused a significant increase in pRCs and trending increase in pACs. Our findings confirmed and expanded upon prior findings.…”
Section: Fed State Increases Proximal Midgut-originating Anterograde ...mentioning
confidence: 71%
“…To promote ab libitum feeding, we followed a 5–7 dpf feeding regimen 19 using chicken egg yolk emulsion 24 . Feeding regimens and nutritional sources are not standardized across labs, 62 but chicken egg yolk is a recently introduced feed 63 that provides sufficient nutrition 64 . We demonstrated that introduction of chicken egg yolk emulsion to larvae between 5 and 7 dpf caused a significant increase in pRCs and trending increase in pACs.…”
Section: Discussionmentioning
confidence: 99%
“…and rotifers ( Brachionus sp.) have been utilized during zebrafish early stages, with variable results in terms of fish survival and growth (Best et al, 2010; Lawrence et al, 2015; Samaee et al, 2021). In either case, live food incorporation in the larvae dietary regime cannot guarantee an adequate nutrient supply that highlights the increasing need of transition to specialized inert diets.…”
Section: Introductionmentioning
confidence: 99%
“…Diet standardization in zebrafish laboratories is often an amalgam of research-based guidelines and oldwives tales. Many different diets are available for use in zebrafish including live feeds such as paramecia, rotifers and artemia, (4)(5)(6) or commercially formulated diets like powders or flakes. (7,8) Although formulated diets offer some level of control over the nutritional content, the nutritional content of live feeds is dependent on what they are fed, which ultimately affects what is available to larvae.…”
Section: Introductionmentioning
confidence: 99%